Obsługa klienta z perspektywy nowoczesnych rozwiązań w zakresie technologii informacyjnych - Binsztok, Aleksander (The customer's service from the perspective of the modern solutions in the range of information technologies, 2006)
In this article the author describes such new solutions in the range of the client’s services as: knowledge management the ways of building the systems of loyalty with customers, using modern information technologies in contacts with clients, new standards in merchandising and cooperation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1132, s. 37-48